Evolutionary game theory based multi-objective optimization for control allocation of over-actuated system - Park, On; Shin, Hyo-Sang; Tsourdos, Antonios (Elsevier, 2019)
This research presents multi-objective optimization for control allocation problem based on the Evolutionary Game Theory to solve distribution of redundant control input on the over actuated system in real-time. Optimizing the conflicting objectives, an evolutionary game theory based approach with replicator dynamics is used to find the optimal weighting using the weighted sum method. The main idea of this method is that the best strategy or dominant solution can be selected as a solution that survives among other non-dominant solutions. The Evolutionary Game Theory considers strategies as a player and investigates how these strategies can survive using replicator dynamics with payoff matrix. The numerical simulation results show the optimal weightings selected by Evolutionary Game and how the payoff has been changed in replicator dynamics.
Keywords: Multi-Objective Optimization; Weighted Sum Method; Evolutionary Game Theory; Replicator Dynamics; Evolutionary Stable Strategy; Control Allocation